157k views
17 votes
PLEASE HURRY!! which expression is equivalent???

PLEASE HURRY!! which expression is equivalent???-example-1
User Jny
by
4.9k points

2 Answers

3 votes

Explanation:

b^(-2) / ab^(-3)

= 1/a * [b^(-2)/b^(-3)]

= 1/a * b = b/a.

P.S. Law of Indices: a^m / a^n = a^(m-n)

User Kinbiko
by
4.1k points
11 votes

Answer:
(b)/(a)

Explanation:

A variable raised to a negative exponent p is equivalent to 1 divided by the variable raised to a positive exponent p.

In this equation, this rule applies to both b variables as follows:


b^(-2) = (1)/(b^2)


(1)/(b^(-3)) = (1)/((1)/(b^3) ) = (b^3)/(1)

After 'solving' for each negative exponent, you can plug them into the previous negative exponents:


(1)/(b^2) * (b^3)/(a) = (b^3)/(ab^2)

Afterwards, cancel out b^2 from the top and bottom of the equation to get your final answer, as b^2 / b^2 = 1


(b)/(a)

User Alea
by
4.4k points